2015
DOI: 10.1080/1331677x.2015.1028244
|View full text |Cite
|
Sign up to set email alerts
|

Legal central bank independence and inflation in various phases of transition

Abstract: The transition environment of 11 EU member countries has created an exceptional opportunity for research on the influence of legal central bank independence (LCBI) on inflation within significantly different circumstances in comparison to developed Western countries. I construct my own transformed GMT (TGMT) model for estimation of the LCBI, researching transition in its early stages and later on, thus comprising the total period of transition. Even in early stages of the transition LCBI has significantly nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The author has also concluded that the higher level of the actual central bank independence is no more correlated to the lower inflation rate once monetary stability is already obtained. Furthermore, Piplica (2015) has also transformed and upgraded GMT model and has researched the influence of the central bank independence to the monetary stability in transition countries EU members in early and in later phase of the transition process. The author has concluded that in the early and in the whole transition period there is a significant negative influence of the legal central bank independence to the inflation, but that this is not so obvious in the latter phase of the transition.…”
Section: Theoretic Considerations and Researches Of The Central Bank mentioning
confidence: 99%
“…The author has also concluded that the higher level of the actual central bank independence is no more correlated to the lower inflation rate once monetary stability is already obtained. Furthermore, Piplica (2015) has also transformed and upgraded GMT model and has researched the influence of the central bank independence to the monetary stability in transition countries EU members in early and in later phase of the transition process. The author has concluded that in the early and in the whole transition period there is a significant negative influence of the legal central bank independence to the inflation, but that this is not so obvious in the latter phase of the transition.…”
Section: Theoretic Considerations and Researches Of The Central Bank mentioning
confidence: 99%